Application of Insulin Medication Management to Improve Blood Glucose Stability in Patients with Type I Diabetes Mellitus - Darma, Aji Setya Guna; .Idramsyah, Idramsyah (GLOBAL HEALTH SCIENCE GROUP, 2024)
People with type 1 diabetes mellitus need insulin therapy to maintain blood glucose stability and improve their quality of life. Nurses have an important role in insulin medication management interventions to achieve therapeutic goals. Objective: This study aims to provide an overview of the application of evidence-based practice nursing activities for developing insulin medication management interventions to improve blood glucose stability in patients with type I diabetes mellitus. Method: This descriptive case study uses a nursing process approach carried out on one young person with type 1 diabetes mellitus at the Regional General Hospital (RSUD) Dr. M Yunus Bengkulu. The nursing process is carried out for three days while the patient is treated in the internal medicine room. Data were collected through interviews and observation. Results: Nursing activities started with assessing the patient's nutritional and fluid needs and continued to data analysis. The analyzed data shows that >80% of the major and minor data are listed in the nursing diagnosis guidelines, namely the Indonesia Nursing Diagnostic Standards (SDKI). From the data obtained, the diagnosis that can be raised is the instability of blood glucose levels with the criteria of nursing outcomes of the level of knowledge with increased expectations. On the last day of the nursing evaluation, there was an increase in the level of knowledge from moderate to increase in the respondents. Conclusions: Applying nursing activity development to insulin medication management intervention effectively achieves blood glucose stability in patients with type 1 diabetes mellitus.